Como as finanças comportamentais e a frequência de uso nas plataformas, impactam no tipo de carteira de produtos do investidor pessoa física - Freitas, Tiago Henrique Maragno Euzébio de (Universidade Federal de São Carlos, 2021)
When deciding how the investor will build his investment portfolio, intrinsic factors such as: age, gender, profession, family, technical knowledge, salary and other factors directly impact the way the investor will invest. Therefore, through a case study added to a descriptive-exploratory research, approximately 350 thousand active accounts were analyzed in an investment broker, and through the study in behavioral finance, it was possible to understand and separate investors on 5 clusters (levels), being: 1st - beginner; 2nd - advanced; 3rd - seniors, 4th - specialists and 5th - DayTrade. This result came from the analysis of the investment portfolio and the frequency of investor interaction on the broker's platforms (website and application).
How behavioral finance and the frequency of use on platforms impact the type of product portfolio of individual investors
Keywords: corretoras de investimentos; investidor; mercado financeiro; crises econômicas; Covid-19; Bolsa de Valores; finanças comportamentais; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO::ADMINISTRACAO DE EMPRESAS::ADMINISTRACAO FINANCEIRA